UNVEILING IRAN'S DETERRENCE BY DENIAL STRATEGY IN RETALIATORY STRIKE AGAINST ISRAEL - Maulana, Muhammad Alfian (Indonesian Journal of International Relations, 2024)
against Israel in March 2024. Grounded in the ‘Deterrence by Denial’ theoretical framework, the research explores Iran’s strategic objectives and the key characteristics of this strategy, including the use of diverse military capabilities, the real-time nature of its threat actions, and the competitive dynamics of the deterrence process. Employing a qualitative approach that relies on a comprehensive analysis of primary and secondary sources, the study reveals that Iran’s primary aim was to persuade Israel that any prospective attack would be both costly and ultimately unsuccessful. The research findings highlight strategic implications and recommendations related to understanding regional conflict dynamics, adapting defence strategies, and the potential for escalation in the Middle East